Redox and Cancer. - Townsend, Danyelle M.; Tew, Kenneth D. (Advances in cancer research, 2014)
Advances in Cancer Research provides invaluable information on the exciting and fast-moving field of cancer research. Here, once again, outstanding and original reviews are presented on a variety of topics, including taxane-anti-androgens cross-resistance in advanced prostate cancer and proteasome inhibitors in the treatment of multiple myeloma.